Müxtəlif ölkələrin tullantı enerji siyasətinin analizi. Davamlı inkişaf üçün təcrübələr - İsmayılova, Günel (My University, 2024)
Waste-to-Energy (WtE) policies vary widely among countries, reflecting different economic, social, and ecological priorities. Several countries have recognized WtE technologies as a key component of their sustainable development strategies to address waste management issues while promoting clean energy production. In Europe, countries such as Sweden and Denmark have been at the forefront of implementing effective WtE policies. Through advanced incineration technologies, these countries have successfully reduced landfill dependency, minimized environmental impacts, and generated renewable energy. In particular, Sweden has reached a point where it imports waste from neighboring countries to meet its energy demand. This approach not only addresses the waste problem but also significantly contributes to their renewable energy mix.
Analysis of waste-to-energy policies in different countries. Experiences for sustainable development
Keywords: Waste energy; Energy policy